2022
DOI: 10.3390/children9071057
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Sleep Medicine: The Important Role of Dental Providers in Detecting and Treating Sleep Disordered Breathing in Children

Abstract: Obstructive sleep apnea (OSA) is a clinical disorder within the spectrum of sleep-related breathing disorders (SRDB) which is used to describe abnormal breathing during sleep resulting in gas exchange abnormalities and/or sleep disruption. OSA is a highly prevalent disorder with associated sequelae across multiple physical domains, overlapping with other chronic diseases, affecting development in children as well as increased health care utilization. More precise and personalized approaches are required to tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Estudos revelam que os principais sinais e sintomas relatados pelos pacientes são a presença de ronco, sonolência diurna excessiva, má qualidade do sono e vários problemas de saúde cardiometabólicos. (DANTAS, et al 2022;Heit, et al, 2022;) Nessa perspectiva, o Cirurgião-Dentista tem grande importância na realização de diversos diagnósticos, visto que dentro do seu estudo/formação e prática clínica está incluso a obtenção de históricos médicos e odontológicos, identificação de estruturas orais anormais, bem como a detecção de doenças bucais, identificação de relações de saúde bucal e sistêmica, inclusive na identificação de sinais e sintomas de bruxismo relacionado ao sono, ronco primário e, sobretudo, no diagnóstico da apneia (SCHROEDER, GURENLIAN, 2019;ANWER et al, 2021;HEIT et al, 2022)…”
Section: Discussionunclassified
“…Estudos revelam que os principais sinais e sintomas relatados pelos pacientes são a presença de ronco, sonolência diurna excessiva, má qualidade do sono e vários problemas de saúde cardiometabólicos. (DANTAS, et al 2022;Heit, et al, 2022;) Nessa perspectiva, o Cirurgião-Dentista tem grande importância na realização de diversos diagnósticos, visto que dentro do seu estudo/formação e prática clínica está incluso a obtenção de históricos médicos e odontológicos, identificação de estruturas orais anormais, bem como a detecção de doenças bucais, identificação de relações de saúde bucal e sistêmica, inclusive na identificação de sinais e sintomas de bruxismo relacionado ao sono, ronco primário e, sobretudo, no diagnóstico da apneia (SCHROEDER, GURENLIAN, 2019;ANWER et al, 2021;HEIT et al, 2022)…”
Section: Discussionunclassified
“…In previous studies that employed the BEARS questionnaire to identify obstructive sleep apnea (OSA) in children, however, it was observed that while the BEARS questionnaire was effective in detecting sleep disturbances, it did not provide any information about other clinical factors that are associated with OSA [21][22][23]. On the other hand, in studies that utilized the FAIRST questionnaire to diagnose OSA in children, the authors reached the conclusion that it is a concise, validated tool that solely relies on clinical evaluation [11,24].…”
Section: Smrmentioning
confidence: 99%
“…In young healthy children, the main etiology of OSA is related to adenoid and/or tonsillar hypertrophy [ 10 ]. However, other factors such as malocclusion or other causes of inflammation such as allergic rhinitis and asthma may also play a significant role [ 10 , 11 ]. Obesity is increasingly more prevalent in the pediatric population and is a significant risk factor for OSA especially in the adolescent group [ 10 ].…”
mentioning
confidence: 99%
“…If the cardiopulmonary coupling can be assessed apriori, this could result in a fundamental shift in the way childhood OSA is managed and treated as the authors point out. Dr. Guillemineault and colleagues had shown that children with OSA required both rapid maxillary expansion and adenotonsillectomy for a complete cure of OSA in children with malocclusion and associated OSA symptoms [ 11 ]. Preventative care to optimize the normal development of maxillofacial skeleton and function to decrease risk of developing OSA is also discussed.…”
mentioning
confidence: 99%
See 1 more Smart Citation